Iowa Ornithologists' Union, Quarterly field report, winter 1986-1987 - Silcock, W. Rosset al; Iowa Ornithologists' Unionet al (1986)
Quarterly field report for the winter 1986-1987 titled "Field reports--winter 1986-1987" contributed by W. Ross Silcock. The report is heavily annotated. A total of 150 species were detected during the winter reporting period. Epson - sheet feed